The Experiences of Trans and Gender Diverse Youth Accessing and Receiving Care in Emergency Departments - Lightfoot, Sophie Emma (Université d'Ottawa | University of Ottawa, 2025)
Despite increased visibility in media and health research, trans and gender diverse (TGD) youth continue to experience worse health outcomes and healthcare experiences than their cisgender peers. Contributing to this issue is the historical and evolving context of cisnormativity and erasure. Although emergency departments often serve as ‘safety nets’ for the medically underserved, emerging research indicates that certain minority groups, including TGD people, report challenges having their needs met in this setting. Barriers to affirming care include a lack of training/education for healthcare providers, including nurses, and a paucity of research about the subjective healthcare experiences of TGD youth. While further research is needed, it must be pursued intentionally. Trans health research is a rapidly growing area of scholarship that, even when well-intended, risks being excessively prescriptive and burdensome to the communities involved. The purpose of this doctoral project was to collaborate with TGD youth to explore their experiences accessing and receiving care in Canadian emergency departments. This project was guided by a pragmatic, critical theoretical framework informed by three theoretical traditions which have been applied to research efforts involving TGD communities: the Gender Minority Stress Framework, erasure, and intersectionality. The methodological approach was a critical participatory action research project with a multi-phase multimethod emergent research design. Community partners were recruited through social media to create a virtual research group. Focus groups were used to elicit guidance from community partners on overall research design and data analysis. The first phase of our study was a cross-sectional survey and online questionnaire. All quantitative data were analyzed using simple descriptive statistics, including range, mean, prevalence, and percentages. Qualitative data were analyzed using summative content analysis and paired with quantitative data to provide context and nuance to the results. Participants reported highly variable experiences in the emergency department with half (n=14, 50%) reporting having avoided seeking needed care out of concern for how they would be treated. These results support the claim that emergency department avoidance is a health concern that is also experienced by TGD youth and set the foundation for the second phase of the study. The second phase was a qualitative study wherein participants were invited to participate in whichever of the following ways felt authentic to them: interview, familial focus group, journaling, and art-based approach. Data were analysed via thematic analysis as described by Braun and Clarke. Participants reported feeling that they were not trusted by healthcare providers to know themselves or their health needs. In response, participants reported employing adaptive strategies to conceal stigmatized aspects of their social location in favour of those that align more closely to social norms. These findings can be understood as examples of epistemic injustice and astute understandings of rhetorical credibility. This doctoral project offers novel theoretical, methodological, and substantive contributions to the fields of transgender health and emergency nursing. Overall, the findings of this dissertation support the assertion that recognizing and supporting the epistemic agency of TGD youth is not only a matter of justice, but also a means of advancing knowledge and promoting improvements in equitable healthcare. Further, this composite work supports calls for intersectional understandings of TGD health and healthcare.
Keywords: Transgender Youth; Emergency Departments; Multimethod Research; Participatory Action Research; Intersectionality; Gender Minority Stress; LGBTQ+ Health